2021
DOI: 10.1186/s12970-021-00445-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of age in the physiological adaptations and psychological responses in bikini-physique competitor contest preparation: a case series

Abstract: The increased popularity of the bikini-physique competitions has not translated to greater research identifying the influence of age on adaptations during contest preparation. The purpose of this case series was to observe how age may influence the adaptations normally seen during preparation and the exploration of newer protocols to address adaptations more relative to the judging standards. Over a 16-week pre-contest preparation, a 32-y bikini competitor (BC) and 44-y master’s bikini competitor (MBC) visited… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 70 publications
(99 reference statements)
0
7
0
Order By: Relevance
“…Despite the well-established health-related issues with low energy availability, none of the three studies that estimated changes in BMD showed a loss of bone mass during pre-contest preparation [ 15 , 16 , 18 ]. The studies comprised a total of four athletes (one male, three females) and used DXA to calculate BMD, which is considered the gold standard for assessment [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the well-established health-related issues with low energy availability, none of the three studies that estimated changes in BMD showed a loss of bone mass during pre-contest preparation [ 15 , 16 , 18 ]. The studies comprised a total of four athletes (one male, three females) and used DXA to calculate BMD, which is considered the gold standard for assessment [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Evidence suggests that a prolonged energy deficit, combined with high levels of exercise and physical activity, can affect anabolic and catabolic hormone levels. In this review, five studies ( n = 8; male = 6; female = 2) reported on testosterone [ 5 , 17 , 20 , 21 , 22 ]; four reported on leptin ( n = 5; male = 2; female = 3) [ 16 , 17 , 20 , 21 ]; three reported on ghrelin ( n = 4, male = 2; female = 2) [ 16 , 17 , 21 ]; three reported on cortisol ( n = 3, male = 2; female = 1) [ 17 , 20 , 21 ]; and two reported on estrogen ( n = 3, female = 3) [ 16 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Longstrom et al observed one female athlete who increased calorie intake post-contest by 97% coinciding with a 22% increase in fat mass and restoration of physiological function within 10 weeks [ 33 ]. A structured gradual increase in energy intake was a strategy observed in 42% ( n = 5) of case studies where athletes followed various protocols to restore pre-contest baseline body fat percentages or to restore energy availability [ 16 , 28 , 33 , 34 , 37 ]. These protocols involved increasing energy availability in a stepwise manner with the target of increasing body mass by 1% per week [ 16 ], or by increasing calorie intake gradually, as seen by Pardue et al where carbohydrate and fat intake were increased by 10–30 g and/or 4–10 g, respectively, each week of the recovery phase up to five months post-contest [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Psychological aspects were observed in five case studies using a range of questionnaires, such as the Eating Attitude 26-item questionnaire (EAT-26), the Profile of Mood States questionnaire (POMS), and other body image and anxiety scales, such as the Body Appreciation Scale (BAS-2), Social Physique Anxiety Scale (SPAS), and the Perceived Stress Scale (PSS) [ 8 , 28 , 35 ]. Anxiety, weight phobia, compulsive self-monitoring, body image concern, and total mood disturbance was generally greatest immediately post-contest and within the first 4 to 8 weeks post-contest [ 8 , 28 , 33 , 35 ]. Psychometric scores trended toward baseline within 6 months post-contest [ 33 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation